The Implementation of E-government in the Sector Transportation (Studi on Area Traffic Control System Program Resources in Sidoarjo District) - Mustika, Muhammad Erlangga Surya; Choiriyah, Ilmi Usrotin; U.B, Ahmad Riyadh (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2022)
ABSTRACT Technological advancements are growing which make the government have to issue policies, due to the large number of road users who create congestion at every intersection in Sidoarjo, the implementation of the Area Traffic Control System (ATCS) program to optimize the implementation of traffic management control systems, in order to create control over traffic violators. traffic and minimize congestion at crossroads. This study aims to determine and analyze resources as for the following indicators; the human resources of the existing officers do their duties and functions well, the budgetary resources are adjusted to local revenues, the equipment resources provide the maximum possible service if there is damage it will be immediately repaired, the authority resources are related to the traffic transportation sector on the road, such as development, development, monitoring, control, and evaluation of communication systems.